A second species of the genus Blythia Theobald, 1868 (Squamata: Colubridae) from Mizoram, India - Vogel, Gernot; Lalremsanga, Hmar Tlawmte; Vanlalhrima, Vanlalhrima (Zootaxa, 2017)
A second species of the genus Blythia Theobald, 1868, Blythia hmuifang sp. nov., is described on the basis of four specimens originating from Mizoram, India. It differs from Blythia reticulata, the other known species in the genus, by having fewer ventral scales (114–117 vs. 129–149), by having fewer subcaudal scales in males (20–21 vs. 22–32), by the greater proportion of tail length/total length (0.109–0.116 vs. 0.075–0.098), by the colour of the venter (bright orange-red in smaller specimens, cream in the largest specimen vs. black in all ages) and the colouration of the supralabials (lower half pale vs. dark), plus other smaller differences in the colouration and the hemipenis. The distribution of Blythia reticulata is discussed. Morphological data of eight recently collected specimens from Mizoram are given and compared to other populations.